Améliorer les conditions d’exercice du management pour réduire les risques psychosociaux - Laurent Karsenty; Pierre Pisani (Activités)
Psychosocial risks increase when work is hindered or even prevented, with no subsequent discussion on work issues or without allowing satisfactory solutions to be found. This may be the case when managers do not benefit from conditions that are essential to the exercise of their function and have difficulty doing their job. Understanding the origin of these difficulties and seeking to remedy them can then become the best way to reduce the psychosocial risks to which employees are exposed. This is the idea that we develop in this article, based on our intervention in a non-profit organization managing a medico-social facility. This intervention was requested by the facility’s Social and Economic Committee (CSE), which had noted an accumulation of complaints from employees since the implementation of a new organization. Based on the analyses carried out during this intervention, several origins of the managers’ difficulties were highlighted, some of which were of a relatively general nature in relation to the managerial function, while others were more specifically linked to the organizational context of the facility. Following these analyses, an action plan was drawn up by a number of the facility’s actors. But above and beyond said action plan, the results of these analyses led us to propose more general measures to improve working conditions for managers.